CONSUMER PURCHASING DECISIONS ON PROCESSED FOOD PRODUCTS DURING THE COVID-19 PANDEMIC - Anisa Aprilia; Heptari Elita Dewi; Andrean Eka Hardana; Imaniar Ilmi Pariasa; Yerho David Hasudungan Harahap; Tissa Permata Prasanti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
This study aims to analyze the determinant factors that influence consumer purchasing decisions during the COVID-19 pandemic. Seventy-five respondents were selected with the criteria of having purchased processed food products made from vegetables and fruits online and offline during the COVID-19 pandemic in Malang. The analytical method used was a regression with the logit model. The dependent variable is the purchase decision, while the independent variables used include social trust (related to handling) to merchants, social trust (related to handling) to couriers, positive information (benefit-centered), negative information (risk-centered), labeling, and government support. The results showed that each variable positively influences purchasing decisions, but only one variable has a significant effect, namely labeling. This research suggests that producers can develop marketing for processed food products by adding complete labeling, such as halal labels.